2014
DOI: 10.3174/ajnr.a3991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Circle of Willis Anatomic Variations on Angiographic and Clinical Outcomes of Coiled Anterior Communicating Artery Aneurysms

Abstract: BACKGROUND AND PURPOSE:Anterior communicating artery aneurysms account for one-fourth of all intracranial aneurysms and frequently occur in the context of A1 vessel asymmetry. The purpose of this study was to correlate circle of Willis anatomic variation association to angiographic and clinical outcomes of anterior communicating aneurysm coiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
5
26
2
Order By: Relevance
“…Underdevelopment of the circle of Willis, which leads to its anatomical variations, can also contribute to weakening of its arteries [18]. It remains significant field of study, with newer research highlighting influence of circle of Willis variations on results of aneurysms treatment [20]. Our results of circle of Willis variations are similar to earlier studies [10].…”
Section: Mca Aneurysmssupporting
confidence: 82%
“…Underdevelopment of the circle of Willis, which leads to its anatomical variations, can also contribute to weakening of its arteries [18]. It remains significant field of study, with newer research highlighting influence of circle of Willis variations on results of aneurysms treatment [20]. Our results of circle of Willis variations are similar to earlier studies [10].…”
Section: Mca Aneurysmssupporting
confidence: 82%
“…In a study on the effects of circle of Willis anatomic variations on angiographic and clinical outcomes of coiled ACOM artery aneurysms, Tarulli et al 13 demonstrated a statistically significant increase in neck remnants and progressive aneurysm sac filling with the A1 dominant configuration, suggesting that this anatomical-hemodynamic feature contributes to aneurysm formation, growth, and instability after coiling treatment. Another study evaluating morphological features of ACOM region aneurysms demonstrated that, among the features studied (direction of the dome, dome size, dome to neck ratio, presence of irregularity, and angle between A1 segment of the anterior cerebral artery and the internal carotid artery), only superior dome direction was associated with incomplete occlusion 10.…”
Section: Discussionmentioning
confidence: 99%
“…Any variation in morphology of CoW alters the occurrence and severity of cerebrovascular disorders, treatment options and recovery. [2][3][4][5][6][7][8] The problem of stroke in India is significantly different from Western World in terms of epidemiology, patterns and presentation. Hence, data from Western literature is not applicable.…”
Section: Introductionmentioning
confidence: 99%